Zvezda . The Star - Ivanov, Aleksandr (LenFilm, 1949)
Duration: 01:32:00 "The Star" is a screen version of a 1947 story by the respected war writer Emmanuil Kazakevich (1913-62) shot in 1949 but released only after Stalin’s death in 1953. Stalin did not agree with the tragic finale, considering that it might ‘deter soldiers from becoming reconnaissance troops’. His demand boiled down to having the soldiers carry out their mission and return to base without loss. All arguments to the effect that such a dénouement would destroy the author's design, reduce artistic quality and subvert characterization, came to naught. As a result the director A. Ivanov tried to reconcile both conclusions, leaving an open-ended finale that allowed the viewer to decide the fate of the soldiers for himself. The picture was saved. (Grigorii Mar’iamov). The film is set in the Spring of 1944, when the Red Army is pushing back the German forces to the Soviet border. The ‘Star’ of the title is the name given to an elite Red Army reconnaissance unit that creates havoc behind the enemy lines. One by one they are picked off, until the final shoot-out against overwhelming odds when the remaining few die heroically, but not before warning their commanders of an impending German counter-offensive which is then repulsed. Kazakevich’s story hints that the soldiers prefer to die rather than return to base and face possible recriminations from the ever-vigilant NKVD, recriminations that could lead to accusations of desertion and cowardice, but this political dimension is glossed over in the film.